(untitled) (Вестник КазНУ. Серия Востоковедения, 2018)
This article describes the implementation of project works in foreign language classroom, which is based on project based learning method. There is always a solution of problem in the project method and it always aims at obtaining the result. The method of projects is thus the organized search, research activity of students, which involves not just the achievement of a particular result, formalized in the form of a concrete practical homework, but the organization of the process of achieving this result. The study shows all the possible variations of organizing projects related to learning languages in an appropriate way.